1.4k views
5 votes
Please please please answer!!!!

Please please please answer!!!!-example-1

1 Answer

2 votes

(1)
12(1)/(2) -9(1)/(4)

Let us convert mixed fraction into improper fraction.


$12(1)/(2) -9(1)/(4)=(25)/(2) -(37)/(4)

Make the denominator same.


$=(25*2)/(2*2) -(37)/(4)


$=(50)/(4) -(37)/(4)


$=(13)/(4)

Now convert improper into mixed fraction.


$12(1)/(2) -9(1)/(4)=3(1)/(4)

(2)
5(3)/(4)-2(5)/(12)


$5(3)/(4)-2(5)/(12)=(23)/(4)-(29)/(12)

Make the denominator same.


$=(23*3)/(4*3)-(29)/(12)


$=(69)/(12)-(29)/(12)


$=(40)/(12)


$5(3)/(4)-2(5)/(12)=3(4)/(12)=3(1)/(3)

(3)
7(1)/(5)-3(7)/(10)


$7(1)/(5)-3(7)/(10)=(36)/(5)-(37)/(10)

Make the denominator same.


$=(36*2)/(5*2)-(37)/(10)


$=(72)/(10)-(37)/(10)


$=(35)/(10)


$7(1)/(5)-3(7)/(10)=3(5)/(10)=3(1)/(2)

(4)
11(2)/(3)-8(1)/(2)


$11(2)/(3)-8(1)/(2)=(35)/(3)-(17)/(2)


$=(35*2)/(3*2)-(17*3)/(2*3)


$=(70)/(6)-(51)/(6)


$=(19)/(6)


$11(2)/(3)-8(1)/(2)=3(1)/(6)

User Miguel Rodrigues
by
5.3k points